Validity of an Instrument to Detect Cheating Confirmed by the Elicited Emotional Reactions - Hernández-Chávez, Paola; García-Campos, Jonatan; Sarabia-López, Saúl; Atilano-Barbosa, Daniel; Rosales-Lagarde, Alejandra; Bautista-Díaz, María Leticia (Frontiers in Psychology, 2021)
Cheating forms part of a complex emotional and cognitive process. However, although a relatively mundane phenomenon, instruments to evaluate cheating and its effect socially are scarce. This paper presents a five-stage approach aimed at providing validity to an instrument designed to assess cheating —specifically, its detection, and emotional reactions towards it once detected. An instrument was designed after (1) reviewing the relevant literature on cheating, in order to (2) design a bank of stimuli, (3) formulate a Delphi panel to judge the most coherent and pertinent ones, and (4) perform three pilot studies to adjust the final version of the instrument. Results from stages 1 to 4 show that content validity was achieved for the Instrument for Detecting Cheating and its Emotional Reactions (INDETRAE, in Spanish: Instrumento para la Detección de Trampa y sus Reacciones Emocionales). Stimuli were grouped into five categories of 18 different scenarios, for a total of 90 vignettes: meaning the INDETRAE is a 5-category, vignette-based questionnaire consisting of contrasting social cost-benefit scenarios, where the cheating situation affects an undefined, a first, or a third person, and also a neutral category with no cheating. In stage (5), several chi-squared tests (p < 0.0005) revealed significant differences between categories, proving that the instrument can indeed be used to detect cheating and to identify differentiated emotional reactions—for example, anger when there was detriment to a third person as opposed to neutral situations, or glad when there was a case of cheating which benefited the first person. The last stage counts as a first approximation to support construct validity of the INDETRAE. The most important contribution of this research consists in developing an instrument to detect cheating, confirmed by the resulting emotional reactions, which therefore demonstrate its validity.